JUST WAR: A TELEOLOGICAL APPROACH AND THE STRATEGIC CONSIDERATIONS OF CARL VON CLAUSEWITZ - Vaksiutenko , Pavlo (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. The article examines the possibility of integrating Carl von Clausewitz’s teleological conception of war with the normative principles of just war theory under the conditions of contemporary hybrid warfare. Particular attention is paid to information aggression and to the ethical challenges arising from informational influence on civilian populations. The aim and tasks. The aim of the study is to develop a teleological approach to just war theory by synthesizing Clausewitz’s strategic conception of war with the doctrines of jus ad bellum, jus in bello, and jus post bellum. The tasks include clarifying the teleological foundations of war in Clausewitz’s philosophy, analysing the ethical criteria of just war theory in relation to hybrid warfare, and determining the moral and legal limits of informational and cognitive influence in the context of the Russo-Ukrainian war. Research methods include philosophical analysis, comparative analysis of classical and contemporary theories of war, elements of international humanitarian law analysis, and case-oriented examination of informational aggression within hybrid conflict. Research results. The study demonstrates that Clausewitz’s conception of war as the continuation of politics by other means provides a teleological basis for evaluating the legitimacy, proportionality, and political purpose of military actions. The integration of strategic teleology with just war theory extends ethical analysis to informational and cognitive dimensions of warfare. The proposed approach establishes criteria for distinguishing legitimate defensive informational actions from aggressive disinformation practices, including proportionality, political legitimacy, verifiability of information, and responsibility for civilian harm caused by manipulative informational influence. The risks of AI-mediated information warfare are also outlined. Discussion. The results indicate that hybrid warfare transforms the classical boundaries between military and non-military forms of conflict. Compared with traditional just war theory, the proposed approach expands ethical analysis toward informational violence and digital forms of aggression. Conclusions. The synthesis of Clausewitzian teleology and just war theory provides a productive philosophical framework for analysing hybrid warfare in the digital age. The proposed approach makes it possible to interpret informational aggression within broader ethical and political categories of contemporary armed conflict and contributes to the philosophical analysis of defensive actions in informational warfare.